Pengaruh Employer Branding, Media Social dan Company Reputation Terhadap Minat Melamar Kerja (Studi Kasus Mahasiswa Zillenial Yang Baru Lulus Kuliah di Kota Bima) - Rizkiatun Ramdina; Rahmatia; Firmansyah Kusumayadi (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the influence of employer branding, social media, and company reputation on the job application interest of zillennial students who have just graduated from college in Bima City. This study uses a quantitative approach with an associative research type. The research sample consisted of 96 respondents determined using the Lemeshow formula. Data collection techniques were carried out through observation, interviews, documentation, and questionnaires with a Likert scale. Data analysis included validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis with hypothesis testing through t-tests and F-tests. The results showed that employer branding, social media, and company reputation significantly influenced the job application interest of zillennial students, both partially and simultaneously. These three variables together were able to explain 66.5% of the variation in job application interest, while the rest was influenced by other factors outside the study. These findings emphasize the importance of strengthening the company's image as an employer, effective use of social media, and maintaining the company's reputation in attracting job seekers from the zillennial generation.